Effects of Sacubitril/Valsartan Versus Irbesartan in Patients With Chronic Kidney Disease: A Randomized Double-Blind Trial. Issue 15 (9th October 2018) - Haynes, Richard; Judge, Parminder K.; Staplin, Natalie; Herrington, William G.; Storey, Benjamin C.; Bethel, Angelyn; Bowman, Louise; Brunskill, Nigel; Cockwell, Paul; Hill, Michael; Kalra, Philip A.; McMurray, John J.V.; et al.
Abstract : Background: Sacubitril/valsartan reduces the risk of cardiovascular mortality among patients with heart failure with reduced ejection fraction, but its effects on kidney function and cardiac biomarkers in people with moderate to severe chronic kidney disease are unknown. Methods: The UK HARP-III trial (United Kingdom Heart and Renal Protection-III), a randomized double-blind trial, included 414 participants with an estimated glomerular filtration rate (GFR) 20 to 60 mL/min/1.73 m 2 who were randomly assigned to sacubitril/valsartan 97/103 mg twice daily versus irbesartan 300 mg once daily. The primary outcome was measured GFR at 12 months using ANCOVA with adjustment for each individual's baseline measured GFR. All analyses were by intention to treat. Results: In total, 207 participants were assigned to sacubitril/valsartan and 207 to irbesartan. Baseline measured GFR was 34.0 (SE, 0.8) and 34.7 (SE, 0.8) mL/min/1.73 m 2, respectively. At 12 months, there was no difference in measured GFR: 29.8 (SE 0.5) among those assigned sacubitril/valsartan versus 29.9 (SE, 0.5) mL/min/1.73 m 2 among those assigned irbesartan; difference, -0.1 (0.7) mL/min/1.73 m 2 . Effects were similar in all prespecified subgroups. There was also no significant difference in estimated GFR at 3, 6, 9, or 12 months and no clear difference in urinary albumin:creatinine ratio between treatment arms (study average difference, -9%; 95% CI, -18 to 1). However, compared with irbesartan, allocation to sacubitril/valsartan reduced study average systolic and diastolic blood pressure by 5.4 (95% CI, 3.4–7.4) and 2.1 (95% CI, 1.0–3.3) mm Hg and levels of troponin I and N terminal of prohormone brain natriuretic peptide (tertiary end points) by 16% (95% CI, 8–23) and 18% (95% CI, 11–25), respectively. The incidence of serious adverse events (29.5% versus 28.5%; rate ratio, 1.07; 95% CI, 0.75–1.53), nonserious adverse reactions (36.7% versus 28.0%; rate ratio, 1.35; 95% CI, 0.96–1.90), and potassium ≥5.5 mmol/L (32% versus 24%, P =0.10) was not significantly different between randomized groups. Conclusions: Over 12 months, sacubitril/valsartan has similar effects on kidney function and albuminuria to irbesartan, but it has the additional effect of lowering blood pressure and cardiac biomarkers in people with chronic kidney disease. Clinical Trial Registration: URL:http://www.isrctn.com . Unique identifier: ISRCTN11958993. Abstract : Supplemental Digital Content is available in the text.